Self‐Assembly of Graphene Oxide on Silicon Substrate via Covalent Interaction: Low Friction and Remarkable Wear‐Resistivity. Issue 3 (27th November 2015) - Mungse, Harshal P.; Tu, Yudi; Ichii, Takashi; Utsunomiya, Toru; Sugimura, Hiroyuki; Khatri, Om P.
Abstract : Few‐layer graphene oxide (GO) is assembled on the silicon surface by a self‐assembly approach via covalent interaction using 3‐aminopropyltrimethoxysilane (APTMS) as a bifunctional chemical linker. X‐ray photoelectron spectroscopy results suggest chemical interactions between oxygen functionalities of GO and amino group of APTMS thin film. The oxygen functionalities of GO thin film are eliminated by vacuum ultraviolet (VUV) photon exposure. Topographic images reveal efficient grafting of GO on the silicon and suggest the presence of few layers in the GO thin film along with wrinkles and folds. Microtribological properties of VUV‐reduced GO (rGO) thin film are probed under the mean contact pressure of 0.3–0.6 GPa. The rGO thin film exhibits low and steady friction (0.12–0.15) compared to that of bare silicon (0.6). The rGO thin film could survive for ≈37 000 laps at 100 mN load, revealing its remarkable wear‐resistivity. Microscopic images and carbon mapping reveal the deposition of delaminated graphene lamellae on the counter steel ball surface. The low friction and excellent wear‐resistivity of rGO thin film are collectively attributed to low‐resistance to shear between the neighboring lamellae of rGO, full coverage and strong interaction of rGO thin film with silicon, and deposition of delaminated graphene lamellae on the counter steel surface. Abstract : Graphene oxide (GO) assembly: Few‐layer GO is assembled on the silicon surface by a self‐assembly approach via covalent interaction. The oxygen functionalities of GO thin film are significantly eliminated by vacuum ultraviolet light. The developed reduced GO thin film exhibits low and steady friction compared to that of bare silicon. Further, it shows remarkable wear‐resistivity and protects the underlying silicon substrate.